Food safety practices in the restaurant industry - Khairatun, Siti Nurhayati, 1975-; Abu Bakar, Ainul Zakiah, 1982-; Abdul Mutalib, Noor Azira, 1985-; Ungku Zainal Abidin, Ungku Fatimah, 1981- (Advances in hospitality, tourism, and the services industry book series., 2022)
"This book provides a series of latest issues relating to food safety management systems as practiced in the restaurant industry around the globe"--